Development and efficacy of a novel mRNA cocktail for the delivery of African swine fever virus antigens and induction of immune responses - Xing Hu; Cong Liu; Nino Rcheulishvili; Yunzhi Wang; Ting Xiong; Fengfei Xie; Xingyun Wang; Ruiai Chen; Peng George Wang; Yunjiao He (Microbiology Spectrum)
ABSTRACT African swine fever (ASF) is a highly lethal infectious disease affecting pigs. Although several vaccine formulations have been developed to protect from ASF virus (ASFV) infection, none have yet provided complete protection without side effects or the risk of progressing to chronic infection. mRNA vaccines offer unparalleled advantages in terms of safety and ability to induce immune responses. In this study, we designed six mRNA vaccines encoding key antigenic proteins of ASFV- B602L, CD2V, EP153R, P30, P54, and P72 and combined them into an mRNA cocktail for vaccination in mice and pigs. Our findings suggest that the mRNA cocktail is capable of provoking robust multivalent humoral and cellular immune responses while maintaining a favorable safety profile. Thus, it may serve as a potential approach for controlling ASF transmission, contributing to the ongoing efforts to develop effective and safe ASFV vaccines. The administration of the mRNA cocktail induced both humoral and cellular immune responses in mice and pigs, suggesting a potential for future ASFV vaccine development.IMPORTANCEThis study explores an mRNA vaccine encoding six critical African swine fever virus (ASFV) antigens (B602L, CD2V, EP153R, P30, P54, P72), demonstrating its ability to induce robust humoral and cellular immune responses in both mice and pigs. This innovative approach serves as a significant advancement in ASFV vaccine development by addressing safety and efficacy concerns. The findings suggest that the mRNA cocktail developed in this study represents a step forward in ASFV vaccine research and development. This strategy holds promise for contributing to ASFV control by offering possibly safer and more effective alternatives to conventional vaccines. This could significantly impact ASF management and prevention strategies globally, ultimately benefiting animal health and reducing economic losses.